Risk factors for death in septic shock: A retrospective cohort study comparing trauma and non-trauma patients. Issue 50 (December 2017) - Medam, Sophie; Zieleskiewicz, Laurent; Duclos, Gary; Baumstarck, Karine; Loundou, Anderson; Alingrin, Julie; Hammad, Emmanuelle; Vigne, Coralie; Antonini, François; Leone, Marc
Abstract : Abstract: The aim of this study was to compare septic shock directly associated-mortality between severe trauma patients and nontrauma patients to assess the role of comorbidities and age. We conducted a retrospective study in an intensive care unit (ICU) (15 beds) of a university hospital (928 beds). From January 2009 to May 2015, we reviewed 2 anonymized databases including severe trauma patients and nontrauma patients. We selected the patients with a septic shock episode. Among 385 patients (318 nontrauma patients and 67 severe trauma patients), the ICU death rate was 43%. Septic shock was directly responsible for death among 35% of our cohort, representing 123 (39%) nontrauma patients and 10 (15%) trauma patients ( P  < 0.0). A sequential organ failure assessment score above 12 (odds ratio [OR]: 6.8; 95% confident interval (CI) [1.3–37], P  = 0.025) was independently associated with septic shock associated-mortality, whereas severe trauma was a protective factor (OR: 0.26; 95% CI [0.08–0.78], P  = 0.01). From these independent risk factors, we determined the probability of septic shock associated-mortality. The receiver-operating characteristics curve has an area under the curve at 0.76 with sensitivity of 55% and specificity of 86%. Trauma appears as a protective factor, whereas the severity of organ failure has a major role in the mortality of septic shock. However, because of the study's design, unmeasured confounding factors should be taken into account in our findings.